Hubungan Kuat Tekan Uniaksial dan Kuat Tarik Tidak Langsung Pada Batuan Sedimen Dengan Nilai Kuat Tekan Rendah - Rizto Salia Zakri; Ilep Prengki; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. Soil and rock material has less strength to tension, compared to pressure and shear. Tensile strength has an important role in the stability of mining activities such as drilling, blasting and making slopes and mine tunnels. Determination of the tensile strength value is currently done by testing the indirect tensile strength (Brazillian Test). In the field commonly, to prediction tension strength value used rule of thumb which is the result of analysis from previous tests, but for this case, the prediction results using rule of thumb are inaccurate. The sample used in this research is sedimentary rock taken from several coal mining locations in the Jambi province. This sample is then tested using a compressive machine to get the uniaxial compressive strength and tensile strength values. Descriptive statistical methods and linear regression methods are used in this study to obtain an accurate prediction of tensile strength based on compressive strength data. According to the descriptive statistical method the tensile strength value is 0.41 times the compressive strength value, while if it is linear regression, the result of the tensile strength value is equal to 0.2079 σc + 0.1917. Both of these methods are able to predict the value of the tensile strength better than the existing rule of thumb, but more advanced research with more samples is needed to get the better equation.Keywords: Sedimentary Rock, Brazilian Test, Tensile Strength, Compressive Strength, Prediction